Synthesis and appraisal of dalbergin-loaded PLGA nanoparticles modified with galactose against hepatocellular carcinoma: In-vitro, pharmacokinetic, and in-silico studies - Gautam, Anurag Kumar; Kumar, Pranesh; Maity, Biswanath; Routholla, Ganesh; Ghosh, Balaram; Chidambaram, Kumarappan; Begum, M. Yasmin; Al Fatease, Adel; Rajinikanth, P.S.; Singh, Sanjay; Saha, Sudipta; M. R., Vijayakumar (Frontiers in Pharmacology, 2022)
Hepatocellular carcinoma (HCC) is a common malignancy which affects a substantial number of individuals all over the globe. It is the 3rd primary cause of death among persons with neoplasm and has the 5th largest mortality rate among men and the 7th highest mortality rate among women. Dalbergin (DL) is described to be effective in breast cancer via changing mRNA levels of apoptosis-related proteins. DL belongs to neoflavonoids, a drug category with low solubility and poor bioavailability. We created a synthetic version of this naturally occurring chemical, DL, and then analyzed it using 1H-NMR, 13C-NMR, and LC-MS. We also made PLGA nanoparticles and then coated them with galactose. The design of experiment software was used to optimize DL-loaded galactose-modified PLGA nanoparticles. The optimized DL-nanoformulations (DLF) and DL-modified nanoformulations (DLMF) were analyzed for particle size, polydispersity index, shape, and potential interactions. In-vitro experiments on liver cancer cell lines (HepG2) are used to validate the anti-proliferative efficacy of the modified DLMF. The in-vitro research on HepG2 cell lines also demonstrated cellular accumulation of DLF and DLMF by FITC level. The in-vitro result suggested that DLMF has high therapeutic effectiveness against HCC. In-vivo pharmacokinetics and bio-distribution experiments revealed that DLMF excelled pristine DL in terms of pharmacokinetic performance and targeted delivery, which is related to galactose's targeting activity on the asialoglycoprotein receptor (ASGPR) in hepatic cells. Additionally, we performed an in-silico study of DL on caspase 3 and 9 proteins, and the results were found to be -6.7 kcal/mol and -6.6 kcal/mol, respectively. Our in-silico analysis revealed that the DL had strong apoptotic properties against HCC.